Particle‐Based Optical Sensing of Intracellular Ions at the Example of Calcium – What Are the Experimental Pitfalls?. Issue 8 (15th December 2014) - Kantner, Karsten; Ashraf, Sumaira; Carregal‐Romero, Susana; Carrillo‐Carrion, Carolina; Collot, Mayeul; del Pino, Pablo; Heimbrodt, Wolfram; De Aberasturi, Dorleta Jimenez; Kaiser, Uwe; Kazakova, Lyubov I.; Lelle, Marco; de Baroja, Natalia Martinez; et al.
<x xml:space="preserve">Abstract</x> Colloidal particles with fluorescence read‐out are commonly used as sensors for the quantitative determination of ions. Calcium, for example, is a biologically highly relevant ion in signaling, and thus knowledge of its spatio‐temporal distribution inside cells would offer important experimental data. However, the use of particle‐based intracellular sensors for ion detection is not straightforward. Important associated problems involve delivery and intracellular location of particle‐based fluorophores, crosstalk of the fluorescence read‐out with pH, and spectral overlap of the emission spectra of different fluorophores. These potential problems are outlined and discussed here with selected experimental examples. Potential solutions are discussed and form a guideline for particle‐based intracellular imaging of ions.